BRANDING AWARENESS “KAMPUS BELA NEGARA” FOR STUDENTS UPN “VETERAN” JAWA TIMUR (Descriptive Analysis of Public Sector Marketing) - Meyga Sisillia; Arimurti Kriswibowo (DIA: Jurnal Administrasi Publik, 2020)
The public sector is all activities carried out by the state apparatus with the aim of meeting the needs of society and solving public problems. UPN "Veteran" Jawa Timur is one of the state universities as a public institution that has branding in marketing. Through branding, it can convey a message to the public and students about the meaning of defending the country itself. However, it turns out that there are still many students who are not aware of the branding of the state defense campus itself. so it is necessary to measure the awareness of the branding of state defense campuses that have never been evaluated by UPN "Veteran" Jawa Timur or abbreviated as UPNVJT. This study aims to measure the level of Branding Awareness of UPNVJT students on the branding of the State Defense Campus. The method used is descriptive quantitative with the technique of collecting data sources obtained by distributing questionnaires. The population in this study were all students of UPNVJT class of 2014-2020, namely 13,915. with a sample to be taken of 389 respondents. The results of this study indicate that branding policies in the public sector are still not supported by the awareness of these public sector managers. The branding awareness of the State Defense Campus is still not at the Top of Mind level so that further treatment is needed to be able to increase public awareness from users.